Prehospital Use of the Intubating Laryngeal Mask Airway in Patients with Severe Polytrauma: A Case Series - Andrew M. Mason (Case Reports in Medicine)
A case series of five patients is described demonstrating the utility of the intubating laryngeal mask airway in the prehospital setting, both as a primary airway rescue device and as a bridge to tracheal intubation. All patients were hypoxaemic, had sustained severe polytrauma and were trapped in their vehicles following road traffic collisions. A probability of survival study showed better-than-predicted outcomes for the group as a whole.